Implementasi Peningkatan Mutu Lembaga Pendidikan Islam Menuju Era 5.0 - Saimima, M Sahrawi; Banawi, Anasufi (IAIN Ambon, 2023)
The implementation of improving the quality of Islamic Education Institutions towards the 5.0 era with the concept of quality that must be used as a benchmark to be applied, is a must in paying attention to it on an ongoing basis. That is why, the purpose of this writing needs to explain it. The method used in this study was used by Systematic Literature Review with four stages, 1) designing a review, 2) conducting a review, 3) analysis, and 4) writing a review. From the research process carried out, it was found that the management of Islamic Educational Institutions towards the 5.0 era, requires management that has entrepreneurial nuances, is based on Communities and Mosques, requires a leadership figure with a transformative, democratic and laissez faire style, then requires a good evaluation system to the improvement of adequate facilities. Then on the side of the Concept of Improving the Quality of Islamic Educational Institutions Towards the 5.0 era, Some of the concepts that can be applied such as 1) the concept of internal and external quality assurance that is responsive and adaptive. 2) Optimization of resources in line with the concept of marketing. 3) Requires the support of all parties, including the role of shops as admirers in Islamic Educational Institutions. 4) Requires orderly governance. and 5) Implementation of digital-based quality planning.